A review in developing body shaping jeans / Aisyah Mohd Yasim, Rosita Mohd Tajuddin and Wan Samiati Andriana Wan Mohd Daud - Mohd Yasim, Aisyah; Mohd Tajuddin, Rosita; Wan Mohd Daud, Wan Samiati Andriana (Universiti Teknologi MARA, 2019)
Most Malaysian women who have bigger lower torso areas, wish to tighten up the hips to enhance the overall shape. However, many Malaysian women encounter difficulty in finding form-fitting jeans that flatter their body shape and smooth out the problematic areas. Despite the pressures of beauty expectation in today’s world, many designers have created garments that accentuate their figure to looking slimmer and curvier at the same time. Thus, this study analyzed the review on designers’ trends and experiments conducted by researchers towards designing body shaping jeans and its potential to accentuate one’s figure besides being stylish and comfortable for daily wear. The production of these attires will help to enhance the innovation in textile design technology while establishing good collaboration between the design experts and manufacturing companies.